Relative energy deficiency in sport (REDs) in elite adult team ball sport athletes: a systematic review - Billingham, T.; Comyns, T. M.; Norton, C.; Warrington, G.; Sweeney, G.; Purtill, H.; Kenny, I. C. (Journal of Science and Medicine in Sport, 2025)
Objectives To investigate the prevalence of Relative Energy Deficiency in Sport (REDs) in elite adult team ball sport athletes and critically evaluate the methods used to assess prevalence.